'Sometimes labels need to exist': exploring how young adults with Asperger's syndrome perceive its removal from the Diagnostic and Statistical Manual of Mental Disorders fifth edition. Issue 4 (20th April 2020) - Chambers, Bethan; Murray, Clodagh M.; Boden, Zoe V. R.; Kelly, Michelle P.
Abstract: The study aimed to ascertain opinions of young adults with Asperger's syndrome (AS) regarding removal of the diagnosis from the Diagnostic and Statistical Manual of Mental Disorders fifth edition (DSM-5). Structured face-to-face interviews were conducted with nine male participants diagnosed with AS before the age of 14. Transcripts were analysed using thematic analysis. Three main themes emerged – 'The AS diagnosis: "a lot of positives"'; 'DSM-5: a step backwards'; and '"What they're doing is stupid as hell": fear, anger, and confusion' – and also several subthemes. Participants broadly rejected the DSM-5 changes and expressed concern about support for people like themselves in the future. Participants also worried about a threat to the 'Aspie' identity that they felt engendered a strong sense of belonging and had been particularly helpful to them on their personal journeys. The findings indicate that the more generalised nature of the new diagnostic criteria is an area of concern.